PENGENDALIAN CACAT AKUSTIK GEDUNG SULTAN SURIANSYAH DITINJAU DARI ASPEK PERANCANGAN ARSITEKTUR - Akbar Rahman (INFO-TEKNIK, 2006)
Acoustic factor in building is one of main factor in room design . this consist of listening and communication between room user. Special building like Opera House, Cinema, meeting room need a special treatment in sound positioning. A distorsion noise will created a bad sound for listener in a room. This conditions call a devective acousting (cacat akustik). For building with this problem need a redesign for a better sound. Redesign need to think for quality of building materials, typology of structure and design. Sultan Suriansyah building the biggest hall in Kalimantan selatan have a problem with this acoustic.  This problem created because of unstable sound diffraction on floor, wall and top side of the building.